Identifying macroeconomic effects of refugee migration to Germany - Enzo Weber; Roland Weigand (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This study investigates causal impacts of immigration on the German economy, explicitly distinguishing refugee and non-refugee migration. We propose a macroeconometric modelling approach complemented by IV techniques. We find that non-refugee migration has more beneficial medium-run effects on GDP and the labour market.
Keywords: F22; E24; C32; 330